Association between breast nodules, anxiety, depression and metabolic risk factors in a Chinese cohort - Long, Yan; Zhang, Wei; Zheng, Maolan; Xie, Qian; Liu, He; Hu, Xiaotong; Zhang, Xuelan; Huang, Wei; Gao, Xia; Jiang, Chunmao; Jiang, Can; Gao, Dong; et al. (Frontiers in Psychiatry, 2023)
Background The relationship between anxiety, depression, and metabolic parameters and the incidence of breast nodules is unclear. This study aims to investigate the association between female breast nodules and anxiety, depression and metabolic factors. Methods This cross-sectional study recruited 857 individuals with biological indicators and breast ultrasound data from the Daping hospital from April 2021 to February 2022. Serum samples were used to measure fasting blood glucose, uric acid, triglycerides, total cholesterol, urea nitrogen, alanine transaminase, aspartate transaminase, albumin, high-density lipoprotein, low-density lipoprotein. Self-rating anxiety scale (SAS) and self-rating depression scale (SDS) were used to assess the level of anxiety and depression. Result The positive rate of breast nodules in women aged 40 to 49 years old was significantly higher than that of other age women. The proportion of participants aged 40–49 years old in the group with breast nodules was significantly higher than that in the group without breast nodules (34.6% vs. 16.9%, p<0.001). Breast nodules in postmenopausal women were significantly lower than those in premenopausal women (26.4% vs. 73.6%, p = 0.026). The SAS scores of women with breast nodules were higher than those of the no-nodules group (40.99 ± 8.45 vs. 38.94 ± 6.89, p<0.001), same as the SDS scores (41.97 ± 10.33 vs. 38.91 ± 7.60, p < 0.001). The number of women suffering from anxiety in the group of breast nodules was significantly higher than that in control (13.8% vs. 4.5%, p < 0.001), and the number of depression in the group of breast nodules was also significantly higher than that of in control (14.4% vs. 4.5%, p < 0.001). Women with breast nodules showed a slightly lower uric acid level than those without breast nodules (290.11 ± 65.32 vs. 301.43 ± 65.93 umol/L, p = 0.016). Multivariable logistic regression analysis showed that age, menopausal status, anxiety and depression status were significantly associated with the presence of breast nodules, but there was no significant difference in uric acid. Conclusion Our findings offer insight into the occurrence of depression and anxiety in the breast nodules of Chinese women. Anxiety and depression status, age and menopausal status may be the independent risk factors for the occurrence of breast nodules.